2009
DOI: 10.1016/j.jpain.2009.01.264
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Expression and Localization at Demyelinated Sites in Painful Human Dental Pulp

Abstract: The expression of sodium channels (NaCh(s)) change after inflammatory and nerve lesions and this change has been implicated in the generation of pain states. Here we examine NaCh expression within nerve fibers from normal and painful extracted human teeth with special emphasis on their localization within large accumulations, like those seen at nodes of Ranvier. Pulpal tissue sections from normal wisdom teeth and from teeth with large carious lesions associated with severe and spontaneous pain were double-stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…This antibody has been widely used in previous studies to identify NaCh clusters at nodes of Ranvier in both CNS and PNS and the staining pattern seen in the current study is consistent with other studies [16,39,40,72]. …”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…This antibody has been widely used in previous studies to identify NaCh clusters at nodes of Ranvier in both CNS and PNS and the staining pattern seen in the current study is consistent with other studies [16,39,40,72]. …”
Section: Methodssupporting
confidence: 91%
“…Results from these studies consistently showed a prominent demyelinating response of axons within the pulpitis samples that resulted in the increased incidence of atypical nodal forms. Our study with the pan-specific NaCh antibody included a quantification of NaCh clusters that lacked caspr and our results showed these "naked" NaCh accumulations were present in both normal and painful specimens [16]. Even though some of these "naked" clusters most likely result from the loss of myelin, their common occurrence in normal specimens as seen in our pan-specific NaCh study and the findings presented here provide additional evidence for their existence in unmyelinated fibers.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Because myelin domains define both cytoarchitecture and molecular signature of A-afferents, demyelination causes electrical instability, ectopic insertion of ion channels, and ultimately, mechanical pain hypersensitivity [2, 5, 41, 42]. In addition to MMP-mediated demyelination, MMPs may regulate the pathogenesis of mechanical allodynia [4] via control of the structural and molecular assembly of myelinated axons.…”
Section: Discussionmentioning
confidence: 99%
“…In myelin gaps (nodes of Ranvier), voltage-gated sodium channel clustering warrants rapid, saltatory conduction [3]. Demyelination of A-afferents contributes to the pathogenesis of mechanical pain hypersensitivity via disruption in this precise molecular and structural signature, including ectopic insertion of ion channels [2, 4, 5]. Among such myelin-related changes contributing to mechanical allodynia we proposed is liberation of myelin auto-antigens, such as myelin basic protein (MBP), leading to the formation of the algesic complexes on A-afferents [6–8].…”
Section: Introductionmentioning
confidence: 99%